Paepalanthus thomasianus, a new species of Paepalanthus subg. Platycaulon (Eriocaulaceae) from São Paulo State, Brazil - Tissot-Squalli, Mara L.; Sauthier, Luana J. (Phytotaxa, 2018)
We describe and illustrate the new species Paepalanthus thomasianus (P. subg. Platycaulon, Eriocaulaceae) from São Paulo, Brazil, and compare it with other morphologically similar species. P. thomasianus is characterized mainly by its leaf indumentum, composed by long multicellular trichomes. Undulations formed by the vascular bundles in the leaf surface and the wide ratio between the leaf base and the middle region of the leaf are also useful to recognize the species. The morphological variation, habitat, geographic distribution, and conservation status of this new species are discussed.